2015
DOI: 10.1016/j.ophtha.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Myopia in Europe and the Impact of Education

Abstract: PurposeTo investigate whether myopia is becoming more common across Europe and explore whether increasing education levels, an important environmental risk factor for myopia, might explain any temporal trend.DesignMeta-analysis of population-based, cross-sectional studies from the European Eye Epidemiology (E3) Consortium.ParticipantsThe E3 Consortium is a collaborative network of epidemiological studies of common eye diseases in adults across Europe. Refractive data were available for 61 946 participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
262
1
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 371 publications
(306 citation statements)
references
References 36 publications
22
262
1
16
Order By: Relevance
“…This is in line with a recently published meta-analysis of population-based, cross-sectional studies from the European Eye Epidemiology (E3) Consortium which showed that the increase in the level of education in younger population did not fully explain the cohort effect of increasing myopia. 32 It is noteworthy with regards to our study that cognitive decline in older people is a different issue compared to the cognitive trajectory in a population based sample and the observation merits further investigation. Regarding the paper by Williams and colleagues 32 one has to keep in mind that the conclusion depended on the assumption that the demands of primary education did not change with age.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This is in line with a recently published meta-analysis of population-based, cross-sectional studies from the European Eye Epidemiology (E3) Consortium which showed that the increase in the level of education in younger population did not fully explain the cohort effect of increasing myopia. 32 It is noteworthy with regards to our study that cognitive decline in older people is a different issue compared to the cognitive trajectory in a population based sample and the observation merits further investigation. Regarding the paper by Williams and colleagues 32 one has to keep in mind that the conclusion depended on the assumption that the demands of primary education did not change with age.…”
Section: Discussionmentioning
confidence: 67%
“…32 It is noteworthy with regards to our study that cognitive decline in older people is a different issue compared to the cognitive trajectory in a population based sample and the observation merits further investigation. Regarding the paper by Williams and colleagues 32 one has to keep in mind that the conclusion depended on the assumption that the demands of primary education did not change with age. In the oldest participants, the task of primary schools was to provide students with minimal numeracy and literacy, but in the post-WW2 period, the task had become to prepare children to go on to complete secondary and even postsecondary education, demanding higher standards.…”
Section: Discussionmentioning
confidence: 67%
“…Shadows are formed at the anterior of the retina so it cannot see distant object clearly. This is due to axial elongation in myopia patient 1 . Increased prevalence of myopia in the world recently, especially in Southeast 1,2 and East Asia (80-90%) 3 is a serious health problem mainly for patients with high myopia 4 .…”
Section: Introductionmentioning
confidence: 96%
“…Myopia could occur as a result of heredity, ethnicity and environment, such as reading habit, often doing close activities 5,6 . Complication of high myopia is macula degeneration, glaucoma, cataract, strabismus and blindness 1 . This condition can decrease the quality of life in children and adult 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the prevalence of myopia is increasing in east and SouthEast Asian countries such as China, Hong Kong, Singapore, and Taiwan (Morgan & Rose, 2005), as well as Western communities such as the United States (Vitale et al, 2009), Australia (Morgan et al, 2012), and Europe (Williams et al, 2015). A potential consequence of myopia is reduced vision, and it is estimated that a quarter of the cases of reduced vision in people living in Western countries is due to myopia.…”
Section: Myopiamentioning
confidence: 99%